A simple semi-distributed water balance model for the Ethiopian highlands - Collick, A.S.; Easton, Z.M.; Ashagrie, T.; Biruk, B.; Tilahun, S.; Adgo, E.; Awulachew, Seleshi Bekele; Zeleke, G.; Steenhuis, Tammo S. (Wiley, 2009)
The discharge of the Nile River is highly dependent on the flow generated in the highlands of Ethiopia. However, little is known about the local (i.e. small scale) watershed hydrological response, due in part to a lack of long duration, continuous hydrological data. The goal of this paper was to develop a realistic, simple model that is useful as a tool for planning watershed management and conservation activities so that the effects of local interventions on stream flow can be predicted at a larger scale. The developed model is semi-distributed in that it divides the watershed into different regions that become hydrologically active given different amounts of effective cumulative rainfall after the start of the rainy season. A separate water balance is run for each of the hydrologic regions using rainfall and potential evaporation as the major inputs. Watershed parameters that were calibrated included the amount of water required before each region becomes hydrologically active, the fraction of soil water that becomes runoff and subsurface flow, and aquifer characteristics, Model validation indicated that daily discharge values were predicted reasonably well with Nash Sutcliffe values ranging from 0•56 to 0•78. Despite the large distance between the test watersheds, the input parameter values for the watershed characteristic were remarkably similar for the humid highlands, indicating that the model could be used to predict discharge in un-gauged basins in the region. As expected, the watershed in the semi-arid region behaved somewhat differently than the other three watersheds. Good quality precipitation data, even for short durations, were key to the effective modelling of runoff in the highland watersheds.